Sistem Monitoring PLTS pada Miniatur PLTH berbasis Mikrokontroler - Permana, Bharata Sena Indra; Aji, Anicetus Damar; Muchlishah; Dezetty Monika (Politeknik Negeri Malang, 2025)
This study focused on the development of a monitoring system for a solar power plant within a miniature hybrid power system, utilizing the ESP32 microcontroller. The system was designed to enhance the efficiency and reliability of solar power monitoring by integrating sensors for light intensity, temperature, and humidity. Sensor data were analyzed and displayed in real time through the Blynk application, enabling practical remote monitoring via mobile devices. The results indicated a significant positive correlation between light intensity and temperature with the electrical power output. The system recorded a maximum voltage of 21,42 V, a maximum current of 1,95 A, and a peak power of 27,2 W from a 50 Wp solar panel measuring 40 cm × 62,5 cm × 2,5 cm, under peak light intensity and temperature conditions. Furthermore, the system effectively identified daily patterns in output power variability. In conclusion, the microcontroller-based monitoring system developed in this study offered an efficient and cost-effective solution for solar power plant management, significantly improving data acquisition and system performance monitoring. These findings contributed meaningfully to the advancement of more efficient and reliable photovoltaic (PV) technology.